Practical use of cloud services for organization of future specialists professional training - Maryna M. Volikova; Tetiana S. Armash; Yuliia V. Yechkalo; Vladimir I. Zaselskiy (Academy of Cognitive and Natural Sciences, 2019)
The article is devoted to the peculiarities of the practical use of cloud services for the organization of qualitative professional training of future specialists. It is established that in order to implement state policy, there is an essential need for using various ICT, in particular cloud services, which are not only economically acceptable in the new educational environment, but also a powerful tools of obtaining new knowledge, skills and abilities. The advantages and disadvantages of using cloud services in the educational process of higher education are substantiated; the examples discuss the methods of using cloud services in the process of studying fundamental disciplines. The object of the study is the professional training of students in higher education institutions. The subject of research is the process of organizing professional training of future specialists with the use of cloud services. To achieve the set goals, a set of general scientific (analysis, synthesis, comparison) and specific scientific (bibliographic, problem-based) was used. Observation and conversation manipulation allowed to highlight the advantages and disadvantages of using cloud services and draw conclusions from the problem under investigation. The foreign experience of using cloud services has been researched and the features of the application of traditional and distance technology training abroad have been determined. It describes the use of the blog as a media-educational technology during the advent of pedagogical practice. The methods of using cloud-based services on the example of creation of a distance course "Linear algebra and analytic geometry" are considered. The prospects of research, which consist in getting acquainted with cloud technologies of the humanitarian profile future specialists at the second higher education, are determined. It has been established that the practical application of cloud technologies in the educational process will promote more qualitative and progressive learning; the formation of a close interaction between the teacher and student; development of professional skills and abilities of independent work.